Strategi Pemasaran Produk Kecantikan Terhadap Peningkatan Penjualan Pada Skincare Wardah Melalui Marketplace Shoope - Anisa Bunga Aprilia; Auranisa Izzati; Anisa Dewi Lestari; Salwa Aristawidya; Dinda Putri Armayani; Ni Nyoman Sawitri (Draf Solusi Indonesia, 2024)
The purpose of this study is to assess the effectiveness of the pemasaran strategy used by Wardah to increase product sales on the Shopee platform. By analyzing sales data and consumer surveys, we can provide information about effective internet marketing strategies for kecantikan products. Temuan indicates that targeted promotional combinations, influencer collaboration, and customer loyalty integration all significantly contribute to the growth of sales. This study identifies that the combination of influencer marketing, time-limited promotions, and personalization of marketing is a key factor in increasing sales. According to the study's findings, a strategy for pemasaran that is integrated and tailored to consumer preferences is crucial for achieving success in a competitive market.